Analisis Resepsi Khalayak pada Konten Keracunan Program Makan Bergizi Gratis (MBG) di Media Sosial TikTok - Nova Nurprianto; Made Dwi Adnjani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study was motivated by the proliferation of viral content on TikTok regarding food poisoning linked to the Free Nutritious Meal Program (MBG) from January to April 2026, which triggered a crisis of public trust. The objective of this study is to determine how the public interprets this content. This study employs Stuart Hall's reception theory, which categorizes audience positions into three groups: dominant, negotiating, and oppositional. The research approach is descriptive qualitative within a constructivist paradigm. Five informants were selected through purposive sampling, representing diverse backgrounds: MBG program recipients, teachers, nutrition students, student activists, and SPPG staff. The research subjects were three TikTok videos from the accounts @bbcnewsindonesia, @sctv_, and @papua.indonesia52. Data were collected through in-depth interviews and documentation, then analyzed using the Miles, Huberman, and Saldana model. The research findings indicate that all informants accepted the factual message that the food poisoning incident did indeed occur and that SPPG failed to maintain hygiene standards. All informants also agreed that SPPG's lack of transparency harmed the public and noted the irony between the program's name,